PENERAPAN METODE PER CONNECTION CLASSIFIER (PCC) PADA PERANCANGAN LOAD BALANCING DENGAN ROUTER MIKROTIK - Dartono Dartono; Usanto Usanto (JEIS: Jurnal Elektro dan Informatika Swadharma, 2021)
The NOC (Network Operation Center) Division is highly dependent on the availability of internet access in carrying out its duties to monitor and maintain the network remotely. Therefore, the absence of adequate internet access will determine the performance of the work performed by the NOC division. However, problems often occur on computer networks or the internet that can hinder the work done by the NOC division, these problems include, such as the process of uploading or downloading files from the server feeling slow, unable to send emails smoothly, connections often experiencing time-out, There is a long network downtime, as well as traffic congestion on the network which can reduce network reliability. To solve this problem, one solution that can be done is to implement load balancing and failover mechanisms on the network using a MikroTik router. This study aims to design a load balancing scheme using the per connection classifier (PCC) method to overcome traffic congestion problems on the network. The research was conducted using field research methods using observation and interview techniques which were conducted from August to December 2020. The results showed that the application of the load balance technique on the xMikrotik router with the PCC (Per Connection Classifier) method can separate the internet connection through the two available ISP lines so that it can solve the problem of traffic buildup on one of the ISP links to reduce latency and improve existing network performance.